Rule of Law in the EU 30 Years After the Fall of the Berlin Wall - Engelbrekt, Antonina Bakardjieva; Moberg, Andreas; Nergelius, Joakim (Swedish Studies in European Law, 2021)
This open access book looks into the evolution and current state of the rule of law in the European Union (EU). The thirtieth anniversary of the fall of the Berlin Wall is chosen as a natural moment of stocktaking; assessing the progress made since the beginning of the democratic reforms in Central and Eastern Europe (CEE), but also critically analysing recent tendencies of rule of law backsliding and open revolt against liberal-democratic values in individual EU Member States. The volume is partly retrospective in that it reflects on the challenges of the post-communist transition and the process of Eastward Enlargement of the Union. Yet it is also prospective, in so far as it reviews the variety of novel mechanisms for strengthening rule of law enforcement in the EU and gauges their potential for bringing sustainable, positive change in this regard. All chapters are written by experienced scholars and practitioners in the field of EU law and policy. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by the Swedish Studies Network.